PENTINGNYA MEMPERTAHANKAN NILAI BUDAYA 5S (SENYUM, SALAM, SAPA, SOPAN, SANTUN) DALAM PENDIDIKAN SEKOLAH DASAR - Risma Ayu Kusumaningrum (PENDIDIKAN SAINS DAN TEKNOLOGI, 2020)
Cultural values ​​that have developed in people's lives lately have declined and began to be forgotten in social life along with the times. Therefore it is important to apply to someone to be able to communicate well from an early age, the role of primary schools is the easiest to implement culture. With that, applying 5S culture (Smiles, Greetings, Accost, Polite, Courteous) to students from an early age of primary school education to instill habits that build students' characteristics well. The purpose of this study is to maintain the importance of 5S cultural values ​​(Smiles, Greetings, Accost, Polite, Courteous) in elementary school education, building good characteristics of the school environment will have a good impact on the community environment. And the application of 5S culture (Smiles, Greetings, Accost, Polite, Courteous) in education. The study used a qualitative descriptive method by taking literature. By maintaining the 5S culture (Smiles, Greetings, Accost, Polite, Courteous) which are introduced from an early age will have a positive impact on the world of education.